Relationship between erythrocyte sedimentation rate and choroidal and retinal thickness in Behçet's disease - Yuvacı,İsa (2019)
ABSTRACT Purpose: To compare retinal and choroidal thickness in patients with Behçet's disease with and without ocular involvement as well as to evaluate the correlation between erythrocyte sedimentation rate and choroidal thickness among patients with Behçet's disease. Methods: This was a prospective interventional study investigating erythrocyte sedimentation as well as choroidal and retinal thickness among patients with Behçet's disease. Patients who were diagnosed based on The International Criteria for Behçet's Disease with (Group A) or without (Group B) ocular involvement and a matched control group (Group C) participated in the study. Optical coherence tomography measurements and blood tests were performed on the same day. Retinal and choroidal thickness were measured using spectral-domain optical coherence tomography (Spectralis, Heidelberg Engineering, Heidelberg, Germany), and central macular thickness, central subfoveal choroidal thickness, and retinal nerve fiber layer thickness were measured using optical coherence tomography. Results: Average erythrocyte sedimentation values were 9.89 mm/h in Group A, 16.21 mm/h in Group B, and 3.89 mm/h in Group C; average central subfoveal choroidal thickness values were 350.66, 331.74, and 325.95 mm, respectively. Average central macular thickness and retinal nerve fiber layer thickness values of patients in Groups A, B and C were 226.39 and 225.97mm; 234.11 and 92.00 mm; and 97.58 and 99.84 mm, respectively. No significant difference was seen between Group A and B patients in central subfoveal choroidal thickness, central macular thickness, or retinal nerve fiber layer thickness values. Central macular thickness was statistically significantly thinner in Groups A and B than in Group C (p=0.016). Group A had thinning in the nasal quadrant of the retinal and general retinal nerve fiber layers when compared with those in Group C (p=0.010 and 0.041, respectively). A connection could not be established between the erythrocyte sedimentation, central subfoveal choroidal thickness, central macular thickness, and retinal nerve fiber layer thickness in the patients with Behçet's disease. Conclusion: The erythrocyte sedimentation rate is typically used to test for activation of Behçet's disease and assess treatment response. In our study, we could not establish a connection between the erythrocyte sedimentation rate and central subfoveal choroidal thickness, central macular thickness, and retinal nerve fiber layer thickness in patients with systematically active Behçet's disease without ocular involvement.